The Economic Conflict between the United States and China and Its Impact on the Arab Gulf Region in Light of the Saudi-Iranian Rapprochement - Hadeel Khalil Mahajneh (Eximia, 2024)
The Middle East, and particularly the Arab Gulf region, holds special importance for the major world powers, especially China and the United States. This has led to the emergence of a covert conflict, akin to the Cold War, between these two nations over the region. In recent years, this conflict between the two global powers has become conspicuously evident, as each seeks to win favor in this vital part of the world. For many decades, the United States has been the strongest and primary ally of the Gulf States. However, China has recently succeeded in penetrating this relationship to establish another strong, close, and robust relationship with the Gulf countries, centered on economic cooperation. In managing its relations with the Gulf states, China relies on diplomatic partnerships, which expand Chinese power and contribute to the decline of American dominance in the Gulf. In recent years, the Gulf states have sought to diversify their political, military, and economic alliances beyond Washington, as part of what is known as a 'hedging policy.' This approach serves as a means to gain political and economic supporters, and, on the other hand, as a power to be used when necessary to exert pressure on Washington. The Chinese rapprochement for economic cooperation with the countries of the region has resulted in comprehensive strategic partnership agreements, especially with the Kingdom of Saudi Arabia, and previously with the United Arab Emirates and Iran in various fields, most notably in energy and infrastructure. In this context, it is natural for there to be ongoing Chinese-Gulf diplomatic communication to achieve rapprochement between the Arab Gulf states, particularly between Saudi Arabia and Iran. Chinese diplomacy has succeeded in restoring Saudi-Iranian relations, ending over seven years of estrangement between the two countries. This was achieved after several rounds of negotiations between the two sides since 2019, under the sponsorship of Iraq and later Oman, in addition to a meeting between the foreign ministers of the two countries on the sidelines of the second session of the Baghdad Conference in Jordan in 2022. China seeks, through the restoration of Saudi-Iranian relations, to break the encirclement that the United States tries to impose on its international activities. Despite this, China has established strategic partnerships with many Gulf countries, especially Saudi Arabia and Iran, both of which have strategic interests with China. This is a reinforcing point for the reality of announcing the resumption of relations. Additionally, the visit of the Chinese president to Saudi Arabia in December 2022 marked an important milestone in strengthening their strategic relations. This visit resulted in building upon comprehensive partnership agreements, with a series of practical executive actions linked to timelines. These include memoranda of understanding aimed at aligning the Chinese Belt and Road Initiative with Saudi Arabia's Vision 2030. The same applies to Iran, where it is linked with China through a 'Comprehensive Strategic Partnership' lasting 25 years, signed in 2021. This partnership includes areas of transportation, especially rail transport, energy, and infrastructure.